Constructing a local approach to journalism education: a study of Zambian educators' conceptualisation of the ideal journalism curriculum - Milupi, Mulako (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2016)
This research is an investigation of Zambian journalism educators' conception of the knowledge, competencies and values that should inform their teaching practice. The study establishes how such educators conceptualise of the purpose of journalism education within the Zambian context. As part of this examination, it identifies characteristics of this context that educators regard to be of relevance to their conceptualisation of such purpose. It then identifies what they understand as the implications for the design of the ideal journalism education curriculum. The study assesses the relevance of these perspectives to the teaching of journalism in Zambia, as an example of an African country with a 'developing' economy. The study draws for its theoretical framework on journalism studies generally and scholarship about journalism education more specifically. It is argued that a review of the global history of journalism education points to the existence of three main traditions of teaching that have developed internationally. The first of these traditions is described as being dedicated to the project of 'professionalisation'; the second to the production of 'critical practitioners', and the third to the project of 'social development'. These traditions are based on different understandings with regard to the principles on which journalism education programmes should be based and the kind of knowledge that they should draw on. It is noted that this body of literature does not include extensive research of the way in which particular groups of African journalism educators respond to these traditions. In order to contribute to such research, the empirical component of this study sets out to explore Zambian journalism educators' conceptualisation of journalism education within their own social context. It does so by means of an exploration of journalism educators based, respectively, at the Evelyn Hone College of Applied Arts (EHC) and the University of Zambia (UNZA)'s Mass Communication Department. The foremost conclusion of the research is that both the professionalising and developmental tradition can be observed to influence the participants' discussion.
Keywords: Uncatalogued